Every buddy counts - Murphy, Stuart J.; Dunbar, Fiona (New York : HarperCollinsPublishers, 1997)
A little girl goes through the day counting her "buddies" which include one hamster, two sisters, three kittens, etc.
Keywords: Counting -- Juvenile literature